Awake videolaryngoscopy versus fiberoptic bronchoscopy. Issue 6 (December 2019) - Moore, Albert; Schricker, Thomas
Abstract : Purpose of review: The difficult airway remains an ongoing concern in daily anesthesia practice, with awake intubation being an important component of its management. Classically, fiberoptic bronchoscope-assisted tracheal intubation was the method of choice in the awake patient. The development of new generation videolaryngoscopes has revolutionized the approach to tracheal intubation in the anesthetized patient. The question whether videolaryngoscopes have a place in the intubation of the difficult airway in the awake patient is currently being addressed. Recent findings: Randomized controlled trials and their meta-analysis have shown that videolaryngoscopes provide similar success rates and faster intubation times when compared with fiberoptic bronchoscope intubation in awake patients with difficult airways. Summary: Videolaryngoscopy is a valid technique that should be considered for difficult airway management in the awake patient.